2023
DOI: 10.1161/cir.0000000000001151
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Strategies for Cardiomyopathy in Children: A Scientific Statement From the American Heart Association

Abstract: This scientific statement from the American Heart Association focuses on treatment strategies and modalities for cardiomyopathy (heart muscle disease) in children and serves as a companion scientific statement for the recent statement on the classification and diagnosis of cardiomyopathy in children. We propose that the foundation of treatment of pediatric cardiomyopathies is based on these principles applied as personalized therapy for children with cardiomyopathy: (1) identification of the specific cardiac p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 178 publications
(297 reference statements)
0
11
0
Order By: Relevance
“…This is in keeping with previous studies that have shown particularly severe cardiac phenotypes in children with NSML 15 and has implications for consideration of novel treatments such as MEK inhibitors, which have shown some promise in the treatment of severe HCM in infants with NS and NSML, 42,43 as recognized by recent guidance. 40,44 A novel finding in this study is the identification of a distinct group of patients with a clinical diagnosis of Noonan-like syndrome, 50% of whom had a variant in a RASopathy gene that was either a VUS or did not fit the clinical syndrome described in the literature, whose features did not fit into one of the other RASopathy syndrome categories. Although their demographics and baseline clinical characteristics were similar to those of the other RASopathy syndromes, they did have a significantly higher prevalence of extra-cardiac manifestations.…”
Section: Correlation Of Clinical Syndrome and Genotype With Cardiac P...mentioning
confidence: 71%
See 1 more Smart Citation
“…This is in keeping with previous studies that have shown particularly severe cardiac phenotypes in children with NSML 15 and has implications for consideration of novel treatments such as MEK inhibitors, which have shown some promise in the treatment of severe HCM in infants with NS and NSML, 42,43 as recognized by recent guidance. 40,44 A novel finding in this study is the identification of a distinct group of patients with a clinical diagnosis of Noonan-like syndrome, 50% of whom had a variant in a RASopathy gene that was either a VUS or did not fit the clinical syndrome described in the literature, whose features did not fit into one of the other RASopathy syndrome categories. Although their demographics and baseline clinical characteristics were similar to those of the other RASopathy syndromes, they did have a significantly higher prevalence of extra-cardiac manifestations.…”
Section: Correlation Of Clinical Syndrome and Genotype With Cardiac P...mentioning
confidence: 71%
“…This is in keeping with previous studies that have shown particularly severe cardiac phenotypes in children with NSML 15 and has implications for consideration of novel treatments such as MEK inhibitors, which have shown some promise in the treatment of severe HCM in infants with NS and NSML, 42 , 43 as recognized by recent guidance. 40 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…In few cases, RCM coexists with systemic arterial hypertension. In these patients, angiotensin converting enzyme inhibitors or non-dihydropyridine calcium channel blockers may be considered [96].…”
Section: What Pharmacological Treatments Are Available For the Most C...mentioning
confidence: 99%
“…In recent decades, emerging studies have assessed the clinical progression of CM, Nevertheless, there remains a scarcity of data on Asian populations [ 3 , 4 ]. The clinical features and profile of CM in the Chinese population may differ from those in other ethnic groups.…”
Section: Introductionmentioning
confidence: 99%